Achievements and Challenges of Political Liberalization in Qatar 1990s onward - Khalil Sardarnia; Hosein Mohseni (رهیافتهای سیاسی و بین المللی)
In this research by using two theories namely structure- agency and needs pyramid of Maslow, has been tried to answer this question: what are achievements and challenges of impediments of political liberalization in Qatar from 1995 onward? The research hypothesis is, Qatar society has been seen some achievements and primitive political liberalization such as in media sphere specially in Aljazeera satellite network, nearly competitive election, primitive expression freedom and reformation in constitution and parliament. But nevertheless have been had serious challenges in this process due to structural reasons such as absence of serious political willingness in sovereignty for deep and comprehensive reformation, socio-political conservative structure, mootness of strong traditional and cultural norms and non- structural reasons such as: weakness of civil agents and assemblies and priority of more people’s welfare-subsistence needs to political liberalization. The main finding of this article follows that: in spite of non-denying of some reformation and primitive political liberalization, this country has had more gap with real and consolidated democracy due to structural challenges and impediments and non- structural one’s among of agents and citizens.